OPTIMIZATION OF LIGHT PORK BURGERS FORMULATED WITH CANOLA OIL AND LINSEED/SUNFLOWER SEED/ALMOND (LSA) MIX - A. Akesowan (Journal of Animal and Plant Sciences, 2015)
The aim of this study was to make a healthier light pork burger containing konjac flour. Two independent variables included (1) the pork fat replacement with canola oil (20-80%, w/w) and (2) added linseed/sunflower seed/almond (LSA) mix (4-10% by pork meat weight) were determined for their effects on the physical properties (cooking yield, peak force, reduction in diameter, emulsion stability and color (L* and a*), as well as sensory quality (color, texture, flavor, taste and overall acceptability) of light pork burgers using response surface methodology (RSM). The optimal process conditions were also investigated. The results showed that the RSM was able to describe how canola oil and the LSA mix affected the physical and sensory properties of light pork burgers made with konjac flour. The development of physical properties such as cooking yield, peak force, reduction in diameter and emulsion stability were pronounced with increasing the amount of canola oil and the LSA mix. However, the product became darker and possessed a strong nutty flavor as a result of the LSA mix, consequently affecting the panelists’ preference. The optimal conditions were to substitute 21.32% of the pork fat with canola oil incorporated with 4% LSA mix.
Keywords: Low-fat meat products; fat replacement; nutritional fortification; konjac flour; response surface methodology